An event study on the impacts of Covid-19 on the global stock markets. (17th June 2021) - Pandey, Dharen Kumar; Kumari, Vineeta
With a sample of 23 developed and 26 emerging market indices using the standard event methodology (Brown and Warner, 1980, 1985), with the market model estimation, the hypotheses that 'Covid-19 cases do not impact the stock market returns' and 'Covid-19 deaths do not impact the stock market returns' have been tested. The empirical results infer that the markets have reacted differently to different events. While the market reaction differs in the case of the first Covid-19 cases detected, the market reaction is similar in the case of the first Covid-19 deaths. The events have negatively and significantly impacted the global stock markets anticipating more severity in the future. The average change in the high-lows of the global indices has been minus 33%. However, this is an initial impact, and the long-term impact will be a topic for future research. The speed of recovery would depend upon how the outbreak is controlled and what are the future policy choices made by the governments.